2012
DOI: 10.1589/jpts.24.581
|View full text |Cite
|
Sign up to set email alerts
|

Selective Activation of the Infraspinatus during Various Shoulder External Rotation Exercises

Abstract: To investigate the selective activation of the infraspinatus muscle while minimizing the use of the posterior deltoid muscles during common shoulder external rotation exercises. [Subjects] Thirty-two ablebodied volunteers (18 males, 14 females; aged 22 to 31 years, mean ± SD, 24.7 ± 3.3 years) were recruited for this study. [Methods] The participants were instructed to perform four exercises: side-lying external rotation; prone abduction with external rotation; sitting external rotation, and sitting with abduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 18 publications
3
18
0
3
Order By: Relevance
“…To maximize the EMG ratio, high infraspinatus activity and low surrounding muscle (middle trapezius, upper trapezius, and posterior deltoid) activity are required. Our results are consistent with those of several previous studies, which reported that SWE is an effective exercise position to isolate the activity of the infraspinatus muscle while minimizing surrounding muscle activity 6,11,14 . There are several possible explanations for our results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…To maximize the EMG ratio, high infraspinatus activity and low surrounding muscle (middle trapezius, upper trapezius, and posterior deltoid) activity are required. Our results are consistent with those of several previous studies, which reported that SWE is an effective exercise position to isolate the activity of the infraspinatus muscle while minimizing surrounding muscle activity 6,11,14 . There are several possible explanations for our results.…”
Section: Discussionsupporting
confidence: 93%
“…shoulder external rotation to strengthen the infraspinatus muscle isolately 2,11 . Adducted shoulder position isolates the infraspinatus from the posterior deltoid, and side-lying external rotation exercise may be the most effective maneuver to increase infraspinatus activity in isolation 5,6 .…”
Section: Isolated Activation Of the Infraspinatus Muscle In Four Manumentioning
confidence: 99%
“…Reinold et al4 ) found that shoulder external rotation in the side-lying position elicits the greatest electromyographic (EMG) activity in the infraspinatus. Findings by Kim et al6 ) show that shoulder external rotation while sitting maximizes the contribution of the infraspinatus, compared to the shoulder abduction with external rotation in the prone position, shoulder external rotation with abduction while sitting, and shoulder external rotation while side-lying.…”
Section: Introductionmentioning
confidence: 97%
“…There are limits to performing activities of daily living and keeping maximum contraction of the muscles, and inputs such as proprioception and visual feedback become damaged11 ) . When rotator cuff injury patients perform humeral external rotation, their movement differs from a normal person’s external rotation, and special measures are needed for this12, 13 ) . Therefore, this study prescribed open kinetic chain exercise (OKCE) and closed kinetic chain exercise (CKCE) for humeral external rotation, to recover muscle endurance and weak muscle strength, at six weeks after rotator cuff repair.…”
Section: Introductionmentioning
confidence: 99%